2007
DOI: 10.1128/aem.01817-06
|View full text |Cite
|
Sign up to set email alerts
|

CO 2 Uptake and Fixation by Endosymbiotic Chemoautotrophs from the Bivalve Solemya velum

Abstract: Chemoautotrophic symbioses, in which endosymbiotic bacteria are the major source of organic carbon for the host, are found in marine habitats where sulfide and oxygen coexist. The purpose of this study was to determine the influence of pH, alternate sulfur sources, and electron acceptors on carbon fixation and to investigate which form(s) of inorganic carbon is taken up and fixed by the gamma-proteobacterial endosymbionts of the protobranch bivalve Solemya velum. Symbiont-enriched suspensions were generated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 38 publications
(42 reference statements)
5
22
0
Order By: Relevance
“…GD1 was isolated from a relatively stable habitat. Scott and Cavanaugh (2007) confirm this conclusion with their studies about chemoautotrophic c-proteobacteria, living as endosymbionts in sulfidic/oxic interfaces. These Solemya velum symbionts have also a relatively narrow range of pH optimum (between pH 7.4 and 8.5), showing the same sharp decline in growth directly below and above these levels.…”
Section: Effects Of Different Ph Values On Chemolithoautotrophic Growthsupporting
confidence: 84%
See 1 more Smart Citation
“…GD1 was isolated from a relatively stable habitat. Scott and Cavanaugh (2007) confirm this conclusion with their studies about chemoautotrophic c-proteobacteria, living as endosymbionts in sulfidic/oxic interfaces. These Solemya velum symbionts have also a relatively narrow range of pH optimum (between pH 7.4 and 8.5), showing the same sharp decline in growth directly below and above these levels.…”
Section: Effects Of Different Ph Values On Chemolithoautotrophic Growthsupporting
confidence: 84%
“…However, in the deeper anoxic zones of the central Baltic basins the DIC concentration is already around 2 mmol L À1 and the pH is 7.1 (Beldowski et al 2010;Schneider 2011) and acidification impacts are therefore assumed to be relatively small in the environment. Only few studies have examined the impact of DIC and pH on growth of chemolithoautotrophic bacteria, mostly with focus on carbon concentrating mechanisms, and using isolates derived from hydrothermal vent habitats (e.g., Dobrinski et al 2005;Scott and Cavanaugh 2007). Therefore, in this study we first investigated whether different DIC concentrations and pH values have an influence on growth of S. gotlandica GD1 T .…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Zbinden et al (2008) observed o30% degraded epibionts in re-pressurised shrimps. The carbon fixation rates determined here are much lower, however, than those obtained for other chemosynthetic symbionts (bacterial homogenates or endobacteria of bivalve gills), for example, those of Bathymodiolus thermophilus: 150 mmolC inc  gC sam À 1  h À 1 in SW (Nelson et al, 1995), or Solemya velum: 2500 mmolC inc  gC sam À 1  h À 1 in the presence of thiosulphate (Scott and Cavanaugh, 2007). Moreover, owing to the relatively low energy level of thiosulphate as compared with sulphide, the latter authors observed threefold higher carbon fixation rates with 0.2 mM Na 2 S (70 mmolC  g prot À 1  min À 1 ) than with 1 mM Na 2 S 2 O 3 (20 mmolC  g prot À 1  min À 1 ).…”
Section: Carbon Fixation By Bacterial Chemosynthesismentioning
confidence: 77%
“…They thus strengthen the view that the relationship between bacteria and shrimp is mutualistic: the epibionts supply carbon compounds to the shrimp and the shrimp, thanks to its gill chamber flow and its swimming behaviour, offers them protection and a supply of chemical compounds, maintaining their position at the oxic/anoxic interface around active chimneys Segonzac et al, 1993). The R. exoculata bacterial epibiosis can thus be regarded as a true mutualistic trophic ectosymbiosis, similar to what is known about the chemosynthetic endosymbiosis of organisms such as R. pachyptila (Felbeck, 1981;Fisher et al, 1989), Calyptogena magnifica (Childress et al, 1991) and S. velum (Stewart and Cavanaugh, 2006;Scott and Cavanaugh, 2007). Finally, the view that bacterial products are assimilated across the shrimp integument rather than via the DT is strongly supported by: (1) the significant incorporation of both 14 C-acetate and 3 Hlysine after an incubation time as short as 1 h. This is insufficient for uptake by ingestion assimilation, which commonly takes several hours (ingestion assimilation of carbon from bicarbonate, for example, requires prior incorporation by the bacteria, followed by grazing of bacteria from the MP) (Chipps, 1998;Hoyt et al, 2000); (2) the high incorporation levels recorded in the gill chamber integument lining (OB, Gi), as opposed to (3) the much lower levels recorded in the DT (Figure 6).…”
Section: Bacteria-host Transfersmentioning
confidence: 87%
“…Although the impact of ocean acidification on microbial communities has been examined in several studies, mainly with respect to the response to elevated pCO 2 , there occur direct and indirect effects simultaneously and we do not have a Figures consistent picture yet (see review by Liu et al, 2010). Only few studies have examined the impact of pH and DIC on growth of chemolithoautotrophic bacteria, mostly with focus on carbon concentrating mechanisms, and using isolates derived from hydrothermal vent habitats (Scott and Cavanaugh, 2007;Dobrinski et al, 2005). However, the effects of DIC and pH were generally not investigated separately, and representative organisms of pelagic anoxic zones were not available until now.…”
mentioning
confidence: 94%